Global incidence and prevalence of bullous pemphigoid: A systematic review and meta‐analysis. (1st February 2022) - Lu, Lingling; Chen, Linjiao; Xu, Yujuan; Liu, Aimin
Abstract: Background: Integrated information on the global prevalence and incidence of bullous pemphigoid (BP) is lacking. Objective: To estimate the incidence and prevalence of BP in a systematic review and meta‐analysis. Methods: Observational studies were included by using databases of Medline, EMBASE, and Cochrane Library. Subgroup analysis was by continent, age, sex, and country income level. Random‐effects model was used. Between‐study heterogeneity was assessed using the I 2 statistic. Results: The global incidence was 0.0419 per 1000 person‐years (95% CI: 0.0414–0.0424). The incidence was 0.047 per 1000 person‐years (95% CI: 0.0462–0.0477), 0.0419 per 1000 person‐years (95% CI: 0.0411–0.0426), 0.0072 per 1000 person‐years (95% CI: 0.0067–0.0078), 0.003 per 1000 person‐years (95% CI: 0.0023–0.0039) in North America, Europe, Asia, and Africa, respectively; 0.0202 per 1000 person‐years (95% CI: 0.0196–0.0208) and 0.0181 per 1000 person‐years (95% CI: 0.0175–0.0188) females and males; 0.001 per 1000 person‐years (95% CI: 0.001–0.001), 0.002 per 1000 person‐years (95% CI: 0.001–0.002), 0.004 per 1000 person‐years (95% CI: 0.004–0.004); 0.007 per 1000 person‐years (95% CI: 0.007–0.008), 0.011 per 1000 person‐years (95% CI: 0.011–0.012), 0.017 per 1000 person‐years (95% CI: 0.015–0.018) for age <50, 50–59, 60–69, 70–79, 80–89, and ≥90 years; 0.0038 per 1000 person‐years (95% CI: 0.0036–0.004112) ( I 2 = 99%, p < .05) and 0.0456 per 1000 person‐years (95% CI: 0.0450–0.0462) ( I 2 = 100%, p < .05). The pooled clinic‐based prevalence was 0.79% (95% CI: 0.75%–0.84%), 1.13% (95% CI: 1.06%–1.21%), 0.21% (95% CI: 0.17%–0.26%), and 0.13% (95% CI: 0.1%–0.15%) for Asia, Africa, and Europe. Conclusions: This study identified the global incidence and prevalence of BP in terms of spatial and population distributions and among various income level. A relatively higher incidence was in Europe, females, older people, and high‐income level country. The prevalence was higher in Asia. These findings should be interpreted with caution due to high heterogeneity of included studies.